2007
DOI: 10.1088/1748-6041/2/4/008
|View full text |Cite
|
Sign up to set email alerts
|

Electrospun nanofibre fibrinogen for urinary tract tissue reconstruction

Abstract: The purpose of this study was to demonstrate that human bladder smooth muscle cells (HBSM) remodel electrospun fibrinogen mats. Fibrinogen scaffolds were electrospun and disinfected using standard methods. Scaffolds were seeded with 5 x 10(4) HBSM per scaffold. Cultures were supplemented with aprotinin concentrations of 0 KIU ml(-1) (no aprotinin), 100 KIU ml(-1) or 1000 KIU ml(-1) and incubated with twice weekly media changes. Samples were removed for evaluation at 1, 3, 7 and 14 days. Cultured scaffolds were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
56
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(57 citation statements)
references
References 30 publications
1
56
0
Order By: Relevance
“…Moreover, cell growth on electrospun scaffolds was better than that on the film scaffolds (Figure 4, PLA vs. PLAF, SHPXL, XL-L, XL-M, and XL-H vs. ZFXL), since the porous structure of electrospun fiber mats was able to facilitate the transportation of oxygen, nutrients, and the metabolic waste of cells, and the migration of cells and communication between them, all of which contribute to better cell growth [15,[39][40][41]. Furthermore, after 24h fewer cells were growing on the electrospun zein fibers cross-linked using SHP (SHPXL) than on samples XL-L, XL-M, and XL-H cross-linked without SHP.…”
Section: Cell Growthmentioning
confidence: 99%
“…Moreover, cell growth on electrospun scaffolds was better than that on the film scaffolds (Figure 4, PLA vs. PLAF, SHPXL, XL-L, XL-M, and XL-H vs. ZFXL), since the porous structure of electrospun fiber mats was able to facilitate the transportation of oxygen, nutrients, and the metabolic waste of cells, and the migration of cells and communication between them, all of which contribute to better cell growth [15,[39][40][41]. Furthermore, after 24h fewer cells were growing on the electrospun zein fibers cross-linked using SHP (SHPXL) than on samples XL-L, XL-M, and XL-H cross-linked without SHP.…”
Section: Cell Growthmentioning
confidence: 99%
“…Preliminary in vitro cell culture with neonatal rat cardiac FBs proved electrospun fibrinogen scaffolds to be extremely bioactive, with the FBs readily migrating through the scaffolds and depositing native collagen [101]. In a similar study with human bladder smooth muscle cells (hBSMs), electrospun fibrinogen scaffolds demonstrated the ability to be degraded and remodeled over a short time course [102]. The rate of scaffold remodeling was so rapid, that seeded scaffolds were cultured in media containing aprotinin, a proteolytic enzyme inhibitor, at varying concentrations (0, 100, and 1,000 KIU/mL) to reduce the rate of scaffold degradation.…”
Section: Electrospinning Fibrinogenmentioning
confidence: 95%
“…HFP was used as the solvent because, not only is it the most widely used solvent in our lab, but it also is very versatile in creating nanofibrous scaffolds from a variety of natural and synthetic polymers without much difficulty. In addition, previously published studies performed by our lab, as well as many others, have shown electrospun scaffolds fabricated from HFP are biocompatible [11,33,[37][38][39][40][41][42]. Once in solution, PRGF was loaded into a 3 mL Becton Dickinson syringe, and placed in a KD Scientific syringe pump (model number 100, Holliston, MA, USA) for dispensing at a rate of 2.5 ml/ hr.…”
Section: Creation Of Eectrospun Prgf Saffoldsmentioning
confidence: 99%
“…The purpose of this study was to create an electro spun scaffold that would harness the reparative potential and bioactivity found in a PRP, namely the growth factor and cytokine milieu contained within, by lyophilizing a PRP and creating PRGF suitable for electro spinning. Utilizing the plasma proteins contained within the PRGF, namely fibrinogen which has been successfully electrospun in the past [33][34][35][36], it was hypothesized that pure lyophilized PRGF could be electro spun into a stable scaffolding material for tissue engineering applications. Such a scaffold, containing a concentration of multiple growth factors and cytokines, would have the potential to promote cellularization of the structure while providing a sustained release of growth factors capable of providing a chemotactic gradient for cellular recruitment.…”
Section: Introductionmentioning
confidence: 99%